"Not everybody approaches it that way": Nurse‐trained health department directors' leadership strategies and skills in public health. Issue 4 (9th March 2022) - Kett, Paula M.; Bekemeier, Betty; Altman, Molly R.; Herting, Jerald R.
Abstract: Evidence points to nurses as possessing particular skills which are important for public health leadership; in particular, investigators have found that a nurse public health director is strongly associated with positive health department performance. To better understand this association and to guide the effective deployment of nurse leaders, researchers sought to explore the specific leadership strategies used by nurse public health directors, using a critical thematic analysis approach to examine these leadership strategies in the context of certain ideologies, power differentials, and social hierarchies. Data were collected via semistructured interviews conducted from July to September 2020 with 13 nurse public health directors from across the United States. Major themes illustrate a distinct picture of the nursing approach to public health leadership: (a) approaching their work with an other‐focused lens, (b) applying theoretical knowledge, (c) navigating the political side of their role, and (d) leveraging their nursing identity . Findings articulate the nurse public health director's distinctive combination of skills which reflect the interprofessional nature of public health nursing practice. Such skills demonstrate a specialized approach that may set nurse leaders apart from other types of leaders in carrying out significant public health work.